Metabolic cost of running is greater on a treadmill with a stiffer running platform - Smith, J. A. H.; McKerrow, A. D.; Kohn, T. A. (Journal of Sports Sciences, 2017)
Exercise testing on motorised treadmills provides valuable information about running performance and metabolism; however, the impact of treadmill type on these tests has not been investigated. This study compared the energy demand of running on two laboratory treadmills: an HP Cosmos (C) and a Quinton (Q) model, with the latter having a 4.5 times stiffer running platform. Twelve experienced runners ran identical bouts on these treadmills at a range of four submaximal velocities (reported data is for the velocity that approximated 75-81% VO2max). The stiffer treadmill elicited higher oxygen consumption (C: 46.7 ± 3.8; Q: 50.1 ± 4.3 ml/kg·min), energy expenditure (C: 16.0 ± 2.5; Q: 17.7 ± 2.9 kcal/min), carbohydrate oxidation (C: 9.6 ± 3.1; Q: 13.0 ± 3.9 kcal/min), heart rate (C: 155 ± 16; Q: 163 ± 16 beats/min) and rating of perceived exertion (C: 13.8 ± 1.2; Q: 14.7 ± 1.2), but lower fat oxidation (C: 6.4 ± 2.3; Q: 4.6 ± 2.5 kcal · min-1) (all analysis of variance treadmill comparisons P < 0.01). This study confirms that caution is required when comparing performance and metabolic results between different treadmills and suggests that treadmills will vary in their comparability to over-ground running depending on the running platform stiffness.